Designing for situation awareness : an approach to user-centered design. - Endsley, Mica R., ....-; Jones, Debra G., ....- (Boca Raton : CRC, 2012)
The barrage of data overload is threatening the ability of people to effectively operate in a wide range of systems including aircraft cockpits and ground control stations, military command and control centers, intelligence operations, emergency management, medical systems, air traffic control centers, automobiles, financial and business management systems, space exploration, and power and process control rooms. All of these systems need user interfaces that allow people to effectively manage the information available to gain a high level of understanding of what is currently happening and projections on what will happen next. They need systems designed to support situation awareness. Addressing the information gap between the plethora of disorganized, low-level data and what decision makers really need to know, Designing for Situation Awareness: An Approach to User-Centered Design, Second Edition provides a successful, systematic methodology and 50 design principles for engineers and designers seeking to improve the situation awareness of their systems' users based on leading research on a wide range of relevant issues.